Modeling the effects of temperature and heterogeneous biting exposure on chikungunya virus disease dynamics. (2022) - Lusekelo, Eva; Helikumi, Mlyashimbi; Kuznetsov, Dmitry; Mushayabasa, Steady
Abstract: Within the last decades, chikungunya virus (CHIKV), a mosquito-borne arboviral disease transmitted by Aedes species mosquitoes has been a growing public health burden. Approximately 1.3 billion inhabitants in 94 countries are estimated to be at risk of chikungunya virus infection. Prior studies suggest that temperature and heterogeneous biting exposure are some of the key determinant factors in transmission dynamics of vector-borne diseases. In order to direct preparedness for future outbreaks, it is imperative to evaluate the effects of heterogeneous biting exposure and temperature variations on transmission dynamics of CHIKV. In this paper, a mathematical model that incorporates heterogeneous biting exposure and temperature effects has been developed and analyzed. The basic reproduction number, an important metric for infectious disease models has been determined. Data from literature has been used to calibrate the model and observed CHIKV data for Kadmat primary health centre, India (2 July to 7 September 2007) has been used to validate the model. Results from the study suggest that disease prevention strategies which are effective at stopping transmission of CHIKV more than 80% of the time, will be highly effective minimizing disease burden during outbreaks. The proposed model can be used to inform policy makers on effective ways of managing CHIKV during outbreaks.